Hypomelanosis of Ito. - Pinheiro, D.; da Silva, S.M.; Caniato Serdeira, A.F. (European Journal of Pediatric Dermatology, 2024)
A case of hypomelanosis of Ito diagnosed at the time of admission to a pediatric intensive care unity due to seizures is presented, emphasizing the importance of dermatological signs for the diagnosis of this neurocutaneous syndrome.